Energy and Resource Allocation: A Dynamic Model of the "Dutch Disease" - Bruno, Michael; Sachs, Jeffrey (Review of Economic Studies, 1982)
It is well known that a domestic resource discovery gives rise to wealth effects that cause a squeeze of the tradeable good sector of an open economy. The decline of the manufacturing sector following an energy discovery has been termed the "Dutch disease," and has been investigated in many recent studies. Our model extends the principally static analyses to date by allowing for: (1) short-run capital specificity and long-run capital mobility; (2) international capital flows; and (3) far-sighted intertemporal optimizing behavior by households and firms. The model is solved by numerical simulation.